Differences Between Men and Women in Self-Reported Body Mass Index and Its Relation to Drug Use - Vera-Villarroel, P; Kuhne-Covarrubias, W (2014)
Background: Obesity is a public health problem of alarming proportions, including among the university population in Latin America. The purpose of this study was to determine the relation between the self-reported body mass index and the associated drug use and health-risk behaviors.Methods: We performed a cross-sectional, descriptive study of 3,311 Chilean university students (17-24 years). The variables weight, height, frequency of physical activity, diet quality index, and drug use were evaluated by way of a self-report questionnaire.Results: 16.7% of students were overweight and 2.1% were obese. Higher rates of overweight and obesity were observed in the men compared to women. There was a significant but moderate association between self-perceived obesity and being men and higher age, and just low with greater use of analgesics and tranquilizers with or without a prescription.Conclusions: The punctual prevalence rates of self-reported obesity, in this sample, are consistent with other Latin American studies. The risk behaviors associated with perceived obesity in terms of gender, particularly the different pattern of drug use, highlight the importance of considering gender when designing strategies to promote health in a university setting. © 2014 Vera-Villarroel et al.; licensee BioMed Central Ltd.